Exosomes derived from mesenchymal stem cells attenuate diabetic kidney disease by inhibiting cell apoptosis and epithelial‐to‐mesenchymal transition via miR‐424‐5p. Issue 10 (29th August 2022) - Cui, Chen; Zang, Nan; Song, Jia; Guo, Xinghong; He, Qin; Hu, Huiqing; Yang, Mengmeng; Wang, Yuanqi; Yang, Jingwen; Zou, Ying; Gao, Jing; Wang, Lingshu; et al.
Abstract: Diabetic kidney disease (DKD) is well‐acknowledged as one of the most common complications in diabetes mellitus. Recent studies have demonstrated the promising role of mesenchymal stem cell‐derived exosomes (MSC‐exos) as a cell‐free treatment strategy for DKD. The present study sought to investigate the therapeutic potential and the underlying mechanisms of MSC‐exos in DKD. The authentication of MSC‐exos was validated by western blot, transmission electron microscope (TEM), and nanosight tracking analysis (NTA). Apoptosis was detected by western blot, TUNEL staining, and flow cytometry. Epithelial‐to‐mesenchymal transition (EMT) was evaluated by western blot and immunofluorescence. The relationship between miR‐424‐5p and Yes‐associated protein 1 (YAP1) was revealed by dual luciferase reporter assay. We observed that MSC‐exos could attenuate DKD by decreasing cell apoptosis and inhibiting epithelial‐to‐mesenchymal transition (EMT) in diabetic kidneys in db/db mice. Besides, we documented that MSC‐exos could reverse high glucose‐induced apoptosis and EMT in HK2 cells. Interestingly, miR‐424‐5p derived from MSC‐exos could inhibit YAP1 activation in HK2 cells, resulting in alleviation of high glucose‐induced cell apoptosis and EMT. Our study provides novel insights into MSC‐exos‐mediated protective effect in DKD. MSC‐exos could inhibit high glucose‐induced apoptosis and EMT through miR‐424‐5p targeting of YAP1.